Effect of Cr content on microstructure, mechanical properties and corrosion behavior of Ti6Al4V alloy produced by selective laser melting. (29th July 2022) - Chen, Guoxia; Zhai, Qiang; Ma, Zhenghang; Yin, Xiaotian; Zhang, Qingxia; Zhou, Hanxiao; Meng, Lingtao; Wang, Kunlun; Wang, Shenghai; Wang, Li
ABSTRACT: In this study, the effect of Cr content on microstructure, mechanical properties and corrosion behaviour of Ti6Al4V alloy produced by selective laser melting (SLM) was investigated. The microstructure exhibited that α' martensite and β phase are obtained in SLM processed Ti6Al4V alloy and Ti6Al4V-Cr system alloys. The increment of Cr content results in the increment of β phase amount. The effect of Cr on the compressive strength and plastic deformation of Ti6Al4V alloy was evaluated by a compression test. The results indicate that the Ti6Al4V+5Cr alloy has a higher compressive strength and superior plastic deformation than that of the SLM processed Ti6Al4V alloy under optimum printing parameters. Meanwhile, the Ti6Al4V+8Cr alloy possesses the best plastic deformation and corrosion resistance. The Ti6Al4V-Cr system alloys, due to the combination of good mechanical properties and corrosion resistant, can be potentially applied in automotive, naval architecture and offshore facility manufacturing.